2006
DOI: 10.1086/503253
|View full text |Cite
|
Sign up to set email alerts
|

MAGPIS: A Multi-Array Galactic Plane Imaging Survey

Abstract: We present the Multi-Array Galactic Plane Imaging Survey (MAGPIS), which maps portions of the first Galactic quadrant with an angular resolution, sensitivity and dynamic range that surpasses existing radio images of the Milky Way by more than an order of magnitude. The source detection threshold at 20 cm is in the range 1-2 mJy over the 85% of the survey region (5 • < l < 32 • , |b| < 0. • 8) not covered by bright extended emission. We catalog over 3000 discrete sources (diameters mostly < 30 ′′ ) and present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
385
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(403 citation statements)
references
References 25 publications
(15 reference statements)
10
385
2
2
Order By: Relevance
“…We will also correlate our data with existing radio surveys in the centimeter range: the NRAO VLA Sky Survey (NVSS, Condon et al 1998), the Multi-Array Galactic Plane Imaging Survey (MAGPIS, Helfand et al 2006), the Sydney University Molonglo Sky Survey (SUMSS, Mauch et al 2003), and the Co-Ordinated Radio "N" Infrared Survey for High-mass star formation (CORNISH) 1 . It will be of particular interest to compare with surveys of the radio continuum and maser emission that will be possible with the Expanded Very Large Array and the 1 http://www.ast.leeds.ac.uk/Cornish/index.html Australia Telescope Compact Array in the near future (Menten 2007).…”
Section: Ancillary Datamentioning
confidence: 99%
“…We will also correlate our data with existing radio surveys in the centimeter range: the NRAO VLA Sky Survey (NVSS, Condon et al 1998), the Multi-Array Galactic Plane Imaging Survey (MAGPIS, Helfand et al 2006), the Sydney University Molonglo Sky Survey (SUMSS, Mauch et al 2003), and the Co-Ordinated Radio "N" Infrared Survey for High-mass star formation (CORNISH) 1 . It will be of particular interest to compare with surveys of the radio continuum and maser emission that will be possible with the Expanded Very Large Array and the 1 http://www.ast.leeds.ac.uk/Cornish/index.html Australia Telescope Compact Array in the near future (Menten 2007).…”
Section: Ancillary Datamentioning
confidence: 99%
“…A comparison of the two catalogs (radio and infrared) allowed the authors to find a sample of 687 radio sources with highly-reliable infrared counterparts. Only 228 of 687 targets were detected in the new MAGPIS at 20 cm (Helfand et al 2006).…”
Section: Sample Selectionmentioning
confidence: 99%
“…However, new radiocontinuum surveys of the galactic plane (Helfand et al 2006;Brogan et al 2006) have recently identified a host of (candidate) SNR in the inner galaxy and surveys searching for signposts of interaction in the 1720 MHz transition of OH have been conducted by Hewitt & Yusef-Zadeh (2009).…”
Section: Introductionmentioning
confidence: 99%